Servo-hydraulic actuator in controllable canonical form: Identification and experimental validation. (1st February 2018) - Maghareh, Amin; Silva, Christian E.; Dyke, Shirley J.
Highlights: A nonlinear model is proposed for hydraulic actuator attached to a physical specimen. A simple technique is proposed to identify the parameters of the model. The nonlinear model has been further transformed into controllable canonical form. The nonlinear model is experimentally validated. Abstract: Hydraulic actuators have been widely used to experimentally examine structural behavior at multiple scales. Real-time hybrid simulation (RTHS) is one innovative testing method that largely relies on such servo-hydraulic actuators. In RTHS, interface conditions must be enforced in real time, and controllers are often used to achieve tracking of the desired displacements. Thus, neglecting the dynamics of hydraulic transfer system may result either in system instability or sub-optimal performance. Herein, we propose a nonlinear dynamical model for a servo-hydraulic actuator (a.k.a. hydraulic transfer system) coupled with a nonlinear physical specimen. The nonlinear dynamical model is transformed into controllable canonical form for further tracking control design purposes. Through a number of experiments, the controllable canonical model is validated.